Pandangan Tokoh-Tokoh Budaya Jawa “Pingit” dalam Film Kartini karya Hanung Bramantyo: Views of Private Java Cultural Figures in The Film Kartini by Hanung Bramantyo - Ernawati, Helni; Santiara S.R, Revinta; Harsa W, Aliffia; Kurniawan, Ahmad (Kibas Cenderawasih, 2024)
This study aims to find out how the seclusion culture took place at that time. This research method is a qualitative descriptive method, because it is subjective by observing the film which is the source of data and analyzing it. The process of collecting data is in the form of notes, screenshot evidence (image capture layers), or excerpts that can be obtained after observing and researching the film carefully. This film was directed by Hanung Bramayanto, played by Dian Sastrowardoyo as Kartini. The analysis technique uses the data analysis model of Miles and Huberman, with data reduction stages (data simplification, choosing which data is important and which is less important). Furthermore, the stage of presenting data in the form of text, charts, graphs, etc., to make it easier for readers to understand. The final stage is concluding, drawing these conclusions based on data from the previous two stages in the form of a light summary. The results of this study are that there are many quotations that discuss how the seclusion culture works. Because the seclusion culture in this era is different from the seclusion culture in ancient times.